2021
DOI: 10.1002/sctm.20-0561
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Successfully Treated with Autologous Granulocyte Colony-Stimulating Factor-mobilized Peripheral Blood CD34-Positive Cell Transplantation: A first-in-Human Report

Abstract: A 36-year-old man with severe acute kidney injury (AKI) was admitted to Shonan Kamakura General Hospital in Japan. He was diagnosed with refractory hypertension based on a severely elevated blood pressure of 224/116 mmHg and retinal, cardiac, and brain damage revealed by electrocardiogram, fundoscopy, and magnetic resonance imaging, respectively. Although hemodialysis was withdrawn following strict blood pressure control by an angiotensin receptor blocker, severe kidney insufficiency persisted. Therefore, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…CD34+ cells have been used in regenerative therapy for several organ damages, including critical limb ischemia[ 27 , 28 ], myocardial ischemia[ 29 ], stroke[ 30 ], and acute kidney injury[ 31 ]. CD34+ cells possess two important properties that are considered necessary for regenerative therapy: Enhanced angiogenic and anti-inflammatory potential[ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD34+ cells have been used in regenerative therapy for several organ damages, including critical limb ischemia[ 27 , 28 ], myocardial ischemia[ 29 ], stroke[ 30 ], and acute kidney injury[ 31 ]. CD34+ cells possess two important properties that are considered necessary for regenerative therapy: Enhanced angiogenic and anti-inflammatory potential[ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to Lee et al , G-CSF-mobilized CD34 + transplantation into the right renal artery is 100% safe and maintains the renal function in a stationary state, suggesting that CD34 + transplantation could mitigate the collapse of renal homeostasis in CKD subjects ( Lee et al, 2017 ). Besides, in phase I/II study, Suzuki and colleagues reported that direct injection of G-CSF-mobilized CD34 + cells to both renal arteries of a 36 years old AKI patient significantly improved the serum creatinine level, GFR, angiogenic-related cytokines, and consequently kidney function 23 weeks after cell therapy without major adverse events ( Suzuki et al, 2021 ). Therefore, CD34 + cell transplantation could apply renoprotective effects by improved angiogenesis and anti-inflammation capability and could be considered a new therapeutic tool for kidney disorders.…”
Section: Clinical Proof Of Concept For Cd34 + Cell...mentioning
confidence: 99%